Nārīcetanā - Bhaṭṭācārya, Tapodhīra (Baṅgīẏa Sāhitya Saṃsada, 2022)
On feminist consciousness in theory and literature in India.
Keywords: Feminism; India.; Feminism in literature.; Bengali literature; History and criticism.